An Efficient Somatic Embryo Liquid Culture System for Potential Use in Large-Scale and Synchronic Production of Anthurium andraeanum Seedlings - Wang, Guangdong; Xu, Chuanying; Yan, Shuo; Xu, Bin (Frontiers in Plant Science, 2019)
Anthurium andraeanum Lind. is the second most important tropical flower in the world flower market. Somatic embryogenesis and plant regeneration in Anthurium has been reported previously; however, a stable and effective method for its commercial use has not been available. In this study, an efficient somatic embryogenesis and liquid culture system for large-scale production of A. andraeanum seedlings was achieved. Building on previous research, this study investigated the main factors for proembryogenic mass (PEM) proliferation, somatic embryo (SE) development, and SE germination in Anthurium. The results showed that relatively low concentrations of plant growth regulators, mineral nutrition, and sucrose promoted PEM proliferation, SE formation, and germination in a liquid culture system. This system can be described as follows: PEMs were induced from leaf blade explants on Murashige & Skoog (MS) medium with half-strength MS macronutrients (1/2 MS) containing 2.0 mg L-1 2,4-dichlorophenoxyacetic acid (2,4-D), 0.5 mg L-1 kinetin (KT), and 3% sucrose and were proliferated in ½ MS liquid medium containing 1.0 mg L-1 2,4-D, 0.5 mg L-1 KT, and 3% sucrose. The highest proliferation coefficients were 5.11–5.16. PEMs were then transferred to MS medium with 1/8 MS macronutrients (1/8 MS) liquid medium containing 1% sucrose to develop into globular embryos and mature embryos. Finally, the mature embryos were placed on four layers of absorbent filter paper saturated with 1/8 MS liquid medium containing 1% sucrose for germination, and an average of 60 seedlings per gram SEs was obtained. This liquid culture system can be used in large-scale and synchronic production of Anthurium seedlings.